Relationships between Plasma Pentraxin 3 Levels and Inflammation Markers Patients with Tunneled Permanent Catheter in Hemodialysis. Issue 5 (September 2015) - Yigit, Irem Pembegul; Dogukan, Ayhan; Taskapan, Hulya; Comert, Melda; Ilhan, Necip; Ulu, Ramazan; Aygen, Bilge
Purpose: Vascular access (VA) devices may contribute to chronic inflammation in hemodialysis (HD). Pentraxin 3 (PTX3) is a recently discovered acute phase protein that responds more rapidly than other inflammatory markers. This study compared PTX3 and other markers between HD patients and healthy controls. Methods: The study population included 30 patients with tunneled permanent catheter (TPC), 30 patients with arteriovenous fistula (AVF) and 30 healthy controls. Hemogram, biochemical assays, ferritin, high sensitive C-reactive protein (hs-CRP), tumor necrosis factor-α (TNF-α) and PTX3 were evaluated in all groups. Results: PTX levels were highest in HD patients with TPC, intermediated in HD patients with AVF and lowest in healthy controls (5.2 + 2.4 vs. 3.1 + 1.3 vs. 1.8 + 0.7, p<0.001 for all comparisons). PTX3 levels correlated strongly to hs-CRP (r = 0.857) and moderately to TNF-α, NLR, ferritin and total neutrophil count. PTX3 and albumin levels had a negative correlation. PTX3 levels were higher in patients with 8 months of TPC than those with 7 months or less. Conclusions: PTX3 levels are significantly elevated in all patients on HD, but presence and extended duration of TPC are associated with incrementally higher levels of PTX3 and other inflammatory markers. PTX3 and NLR may be useful in assessing chronic inflammatory states in HD.